The Origin of the Indonesian Blasphemy Law and its Implication towards Religious Freedom in Indonesia - Siddik, Syahril (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
This article elucidates the chronology of the insertion of Undang-Undang Penistaan Agama (‘the Indonesian blasphemy law’) in Kitab Undang-undang Hukum Pidana (‘the Indonesian Criminal Code,’ later mentioned as KUHP). The law aims to prevent a religious elements; such as holy books, rituals, saints, etc. from offences. In the postauthoritarian Indonesia, this law has been used to ban individuals and minority groups by religious groups, state apparatus, and politicians. This has caused a dispute and debate in the society because there are several groups most of whom are intellectuals and human rights activists, who consider that the law is against Undang-Undang Dasar 1945 (‘the Indonesian Constitution 1945,’ later mentioned as UUD 45). They have urged the government through Mahkamah Konstitusi (‘the Constitutional Court of Indonesia,’ later mentioned as MK) to remove or revise it. This article attempts to answer the questions of how blasphemy law is formulated and then inserted in the Criminal Code and how it has defined religious freedom in Indonesia. Its aim is to understand the historical aspects of the law and the interpretation of religious freedom in Indonesia. The data of this article were collected through library research (books, newspapers, articles, CDs, etc.) and ethnography (observation and interviews). The results show that the Indonesian government has struggled to locate the definition of religious freedom and tend to be inconsistent in dealing with dispute of blasphemy law. In many cases, it ends in favor with the more powerful voice in public.